INTERACTION OF 3-HYDROXY PYRIDINE AND SURFACTANT MICELLES: A FLUORESCENCE STUDIES - MAHLAWAT, ANSHU; GOYAL, ARUN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Micellar solubilization is a powerful alternative for dissolving hydrophobic compound in aqueous environment. 3-hydroxy pyridine (3- HP) derivatives are the potential endogenous photosensitizers. 3-HP derivatives show protective effect in clinical extreme condition such as hypoxia, hyperthermia, hypokinesia. Micellization of 3-HP followed by solubilization would catalyze its pharmaceutical activities which may serve better results in medicinal and analytical fields. Methods: Fluorescence and absorption spectroscopy techniques are used to monitor the micellar solubilization studies of 3-HP. Solubilization studies of 3-HP with various anionic, cationic and nonionic surfactants have been performed in aqueous medium around 23–25°C temperature. The solubilization action of the surfactant has also been determined by theoretical calculated spectral parameters such as empirical fluorescence coefficient, quantum yield, stokes, shift and molar absorption coefficient. Results: 3-HP shows fluorescence excitation peak at 315 nm and emission peak at 390 nm respectively while the absorbance of 3-HP has been found to be maximum at 305 nm. The fluorescence as well as the theoretically calculated spectral data has been used to characterize the hetero environment of the micelles in terms of their polarity, probe solubilization site and critical micelle concentration. Conclusion: This article briefly discusses the importance of surfactants in biological system model as well as the use of micelles in pharmacy as an important tool that finds numerous applications.